Effects of environmental heat stress (35°C) with simulated air movement on the thermoregulatory responses during a 4-km cycling time trial - Altareki, N.; Drust, B.; Atkinson, G.; Cable, T.; Gregson, W. (International Journal of Sports Medicine, 2009)
The aim of the present investigation was to examine the influence of environmental heat stress (35 °C) on 4-km cycling time trial performance using simulated environmental conditions and facing air velocities that closely reflect competitive situations. Nine competitive cyclists (age 34 ± 5 years, maximal oxygen uptake 61.7 ± 8.6 ml · kg-1 · min-1) completed a simulated 4-km cycling time trial in laboratory ambient temperatures (dry bulb temperatures) of 35 °C and 13 °C (relative humidity 60 %, air velocity 5.6 m/s). Mean performance time was reduced in 35 °C (390.1 ± 19.6 s) compared to 13 °C (382.8 ± 18.2 s) (95 % CI of difference = 4.0 to 10.6 s; p < 0.01). This was consistent with a decline in mean power output throughout the duration of exercise in 35 °C compared with 13 °C (p < 0.01). Mean skin temperature and mean body temperatures were elevated at rest and throughout the duration of exercise in 35 °C (p < 0.01). A higher level of muscle temperature was also observed at the onset and cessation of exercise in 35 °C (p < 0.01). The rate of heat storage (35 °C, 413.6 ± 130.8 W · m-2; 13 °C, 153.1 ± 112.5 W · m-2) representative of the entire 4-km time trial was greater in the heat (p < 0.01). When expressed per kilometre, however, difference in the rate of heat storage between conditions declined during the final kilometre of exercise (p = 0.06). We conclude that the current decrements in self-selected work-rate in the heat are mediated to some extent through afferent feedback arising from changes in heat storage at rest and during the early stages of exercise which serve to regulate the subsequent exercise intensity in attempt to preserve thermal homeostasis.